Investigation of interpolation algorithms for computer identification of dynamic models on experimental data - Костьян, Наталья Леонидовна (Technology audit and production reserves, 2015)
Despite the large number of developed algorithms of identification of dynamic models of transient, still little attention was paid to the computer implementation of iterative methods for the problem of identification of the transfer function for the transient response based interpolation algorithms approximation. This article provides an analysis of variational and interpolation algorithms for solving the problem of identification of an aperiodic transient object with a self-leveling, it is developed a set of programs that implements the algorithm of variational modeling in modern MATLAB system through combination of symbolic mathematics and calculations. The selected algorithm allows providing a certain amount of independence of members in terms of approximating the number of interpolation points. The article describes the software system, and describes the results of test examples that show a large approximation error in the initial part of the transition process. The obtained results can serve as the basis for the creation of combined iterative interpolation algorithm in the study of transient stability of dynamical systems.